2022
DOI: 10.1186/s12893-022-01852-0
|View full text |Cite
|
Sign up to set email alerts
|

Negative appendectomy rate in patients diagnosed with acute appendicitis

Abstract: Background Acute appendicitis is the most common cause of acute lower abdominal pain leading patients to the emergency department. This study aims to find the negative appendectomy rate in patients diagnosed with acute appendicitis from 2015 to 2019. Methods This study was a retrospective cohort study in the patients preoperatively diagnosed with acute appendicitis and underwent appendectomy from January 2015 to December 2019. Negative appendectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…Though this is in contrast to some of the existing literature. 8, 19,24,25 , other studies have suggested WBC is not a predictor of AA. 26 Furthermore it has been suggested that WBC is a poor predictor of AA due to an unreliable speci city and sensitivity and there is no consensus for a reliable cut off value.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Though this is in contrast to some of the existing literature. 8, 19,24,25 , other studies have suggested WBC is not a predictor of AA. 26 Furthermore it has been suggested that WBC is a poor predictor of AA due to an unreliable speci city and sensitivity and there is no consensus for a reliable cut off value.…”
Section: Discussionmentioning
confidence: 93%
“…8,22-25 Also in keeping with other literature we found advancing age to be negatively associated with a negative appendicectomy. 8,17,19,[22][23] This may be due to older patients being more likely to undergo cross-sectional radiological imaging to exclude other diagnosis that can mimic AA or identify any underlying pathology that may cause AA in older patients. 4 The ndings in this study cohort have suggested USS is of no discernible bene t in paediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute appendicitis is still often misdiagnosed, and the negative appendectomy rate remains high [ 19 ]. In most studies, the negative appendectomy rate is less than 10% [ 20 , 21 ], but in some reported studies, it is higher—about 10–15% [ 9 ] and can exceed 20% [ 19 ]. A negative appendectomy rate is not reported in our study because in our database [ 18 ], only patients with a confirmed diagnosis of acute appendicitis who underwent laparoscopic appendectomy were included.…”
Section: Discussionmentioning
confidence: 99%
“…Negative appendicectomy refers to surgical removal of the normal appendix on nal pathological report [4]. The Second Australian Atlas of Healthcare Variation in 2017 revealed that negative appendicectomy rates in Australia were 21-24% [5 ].…”
Section: Introductionmentioning
confidence: 99%